International Trade and Food Security the Future of Indian Agriculture. - Brouwer, Floor (CAB International, 2016)
This book explores structural changes in India's agrifood systems during the next ten to twenty years. The dynamics in the agrifood sector is explored in the context of the overall economy, taking into account agricultural and trade policies and their impacts on national and global markets.